Examining the Effects of Nebraska's Good Time Laws - Research Brief - Cain, Calli M. (2014)
The purpose of this research brief is to summarize the findings of a study of Nebraska’s good time laws conducted by Dr. Benjamin Steiner and Calli Cain for the Nebraska Center for Justice Research at the University of Nebraska-Omaha. An electronic copy of the full report can be accessed through the link at the end of this brief. This brief lists each of the three specific research questions, the primary findings for each question, and the major conclusion from each set of findings. Please refer to the full report for the executive summary, full findings, and methodological details of the research project